Total Phenolics and Flavonoids Content of Pemphis acidula Leaves Extract, In Vitro Antioxidant and Antidiabetic Activity, and Characterization of The Extract Towards Standardized Antidiabetic Herbal Medicine - Mardianawati, Nurlita; Sulastri, Lilik; sinaga, ernawati (Universitas Tidar, 2024)
Diabetes mellitus is a prevalent metabolic disorder that still remains a threat to public health all over the world. Oxidative stress is a critical factor in the pathogenesis and progression of diabetes mellitus and its associated complications. Plants contain many antioxidant compounds that can provide protection against free radical-related diseases. The present study aims to evaluate the potential of ethanol extract of Pemphis acidula leaves as antidiabetic agent by measuring its total phenolics and flavonoids content, and its antioxidant and α-amylase inhibitor activity as well. The total phenols content was determined using Follin-Ciocalteu method and total flavonoids content was determined using the AlCl3 colorimetric method, while in vitro antioxidant activity was evaluated using DPPH method. Results of the study showed that ethanol extract of Pemphis acidula leaves contains total phenolics and total flavonoids equivalent to 5390mg GAE/100 grams of extract and 581.66mg QE/100 grams of extract respectively, and it had also been proven that the extract has strong antioxidant and α-amylase inhibitor activity with IC50 of 57.71 ppm and IC50 of 70.05 ppm respectively. From these results, it can be concluded that ethanol extract of Pemphis acidula leaves has the potential as an anti-diabetic agent.